The Influence of Green-Blue Economy-Based Entrepreneurship Education on Santri Self-Efficacy and Independence - Nuraeni; Didin Nurul Rosidin; Eti Nurhayati; Siti Fatimah (Women, Education, and Social Welfare, 2026)
Islamic boarding schools are increasingly expected to integrate religious formation with sustainable entrepreneurial competencies that support students’ socio-economic independence. This study examined the influence of Green–Blue Economy-based entrepreneurship education on santri self-efficacy and independence at Ma’had Al-Zaytun, Indramayu, Indonesia. A quantitative explanatory survey design was used, involving 55 twelfth-grade santri selected from a population of 188 through cluster random sampling. Data were collected using a five-point rating-scale questionnaire and analyzed using simple linear regression after normality and linearity assumptions were met. The findings showed that Green–Blue Economy-based entrepreneurship education positively and significantly influenced self-efficacy, explaining 48.4% of its variance, and santri independence, explaining 51.3% of its variance. The stronger contribution to independence indicates that sustainability-oriented entrepreneurship learning is especially relevant for developing practical autonomy, responsibility, and readiness for productive participation. These findings imply that pesantren can strengthen graduate quality by integrating ecological agriculture, maritime skills, Islamic values, and practice-based entrepreneurship into a sustainability-oriented curriculum.